PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIC SMPIT AZ-ZUHRA PEKANBARU - Noviani Riska Sipahutar; Susda Heleni; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This classroom action research is aimed at improving learning process and improving mathematics learning outcomes by implementing Cooperative Learning  with Structural  Think Pair Square Approach. The research subjects are 24 heterogenous academic ability level students of the VIIC class of Islamic Junior High School Az-Zuhra Pekanbaru in academic year of 2015/2016. The research consisted of two cycles in which each cycle consisted of four phases, i.e; namely planning, implementing, observing, and reflecting. By the end of a cycle, daily test was held. The data was collected by means of observation and daily test. The action success indicators were if there is learning process improvement and the increasing number of students passing Minimum Completeness Criteria (MCC) in daily test I and daily test II. The research shows that teachers and students’ activities were conducted well as planned. Most of the students participated actively in the learning process e.g. discussing, presenting student’s worksheet, responding to classmate’s presentation, and drawing the lesson conclusion. Additionally, the students afforded to answer the written test given by teacher well. Therefore, it can be said that improvement of learning process took place in every meeting. Furthermore, the number of students passing the MCC on base score, daily test I (first cycle), daily test II (second cycle) were respectively 9 students (35%), 10 students (41,67%), dan 17 students (70,83%). The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increase. Finally, the research also shows that  cooperative learning with structural  Think Pair Square  approach can improve mathematic learning process and learning outcomes of VIIC class students at Islamic Junior High School Az-Zuhra Pekanbaru.